THE USE OF LOW-INTENSITY RADIATION IN TREATMENT OF PERIODONTAL TISSUE DISEASES (LITERATURE REVIEW) - E.M. Danko; Ye.Ya. Kostenko; S.B. Kostenko; V.V. Pantyo (Український стоматологічний альманах, 2021)
Topic relevance. Periodontal tissue diseases currently take a significant place among infectious diseases, both in dentistry and in medicine in general. Traditional methods of treatment of inflammatorydystrophic periodontal diseases do not bring the desired results, so the question arises of finding alternative, non-drug treatments. Among such means, special attention is paid to the use of various types of low-intensity radiation, as well as the cumulative effect of light and photosensitizers.